Terahertz Multicolor Imaging of Opaque Objects Using Self-Mixing Interferometry with Quantum-Cascade Lasers - Jiaxuan Cai; Yan Xie; Yingxin Wang; Meng Chen; Lianhe Li; Mohammed Salih; Edmund H. Linfield; Ning Yang; Weidong Chu; Peng Bai; Ziran Zhao (Photonics)
Self-mixing interference in a terahertz quantum-cascade laser has been demonstrated to be suitable for the detection of weak signals scattered or reflected by the target. This technology has achieved the high-sensitivity detection of complex refractive indices, surface/interface morphologies and molecular feature spectra. Here, a set of terahertz quantum-cascade lasers with different lasing frequencies is used to inspect a tiny amount of powder concealed inside a polytetrafluoroethylene tablet by using self-mixing interferometry combined with the penetration properties of terahertz waves. Multicolor spectral images were acquired, which were synthesized by absorption contrast images obtained at different lasing frequencies. They enable the detection of the spatial distribution of hidden objects which are totally opaque in visual light and allow for them to be identified with spectral absorption characteristics. Self-mixing interference technology can also obtain phase information when a terahertz wave interacts with a tablet, showing the difference between the hidden object and surroundings from another dimension. Our research may provide a strategy for the development of terahertz multispectral imaging technology for the inspection of hidden trace residues.